A new subtidal species of the genus Petrolisthes Stimpson, 1858 (Crustacea: Decapoda: Porcellanidae) from Okinawa, with an account of species of the genus known from the Ryukyu Islands, southwestern Japan - Osawa, Masayuki; Uyeno, Daisuke (Zootaxa, 2013)
A new porcellanid crab, Petrolisthes uruma sp. nov., is described based on a single specimen collected from Okinawa-jima Island in the Ryukyus, southwestern Japan. The unique holotype was collected from a subtidal depth of 10 m, though vast majority of the genus occur in intertidal to shallow subtidal zone. The new species is morphologically closest to P. moluccensis (De Man, 1888), but is distinguished by the weaker striation on the carapace, the proportionally longer carpus of the cheliped, the number of the anterior marginal teeth of the carpus of the cheliped, and the meri of the second and third pereopods each with a much stronger spine at the lateroventral distal angle. A brief note on species of Petrolisthes presently known from the Ryukyu Islands is given.